Kecanggihan Information And Communications Technology (ICT) Dalam Proses Belajar Mengajar - Mutmainah, Mutmainah (Universitas Merdeka Madiun, 2019)
The development of information and communications technology makes easy to find information needed from the world. Included in the student learning process. ICT has an important role in education ICT sophistication facilitate student-centered learning (SCL). However, can ICT create an effective and efficient learning process? What does the negative and positive effect of sophistication information and communications technology (ICT) in learning process? How effect on personal ethics? How should the role of government to solve that negative effect? This research uses a qualitative method with a phenomenology approach. This approach is a research-based on observations of phenomenology that occur in Merdeka University of Madiun. The data analysis uses descriptive techniques. It’s the result of the data collection from some informants were concluded. The results of research show that negative effects of development ICT; 1) decreasing student ethics, 2) learning process not effective, 3) student doesn’t ready to study in the classroom, 4) and delay next job. The positive effect is easy to get course material and reach communications quickly. The government role to solve negative effect are 1) socialization about ICT usage, 2) limit user age from government, 3) blocking web that no match with user age and 4) socialization about controlling child.